Therapeutic Effects of the Superoxide Dismutase Mimetic Compound MnIIMe2DO2A on Experimental Articular Pain in Rats. (1st September 2013) - Di Cesare Mannelli, Lorenzo; Bani, Daniele; Bencini, Andrea; Brandi, Maria Luisa; Calosi, Laura; Cantore, Miriam; Carossino, Anna Maria; Ghelardini, Carla; Valtancoli, Barbara; Failli, Paola
Abstract : Superoxide anion (O 2   − ) is overproduced in joint inflammation, rheumatoid arthritis, and osteoarthritis. Increased O 2   − production leads to tissue damage, articular degeneration, and pain. In these conditions, the physiological defense against O 2   −, superoxide dismutases (SOD) are decreased. The Mn II complex MnL4 is a potent SOD mimetic, and in this study it was tested in inflammatory and osteoarticular rat pain models. In vivo protocols were approved by the animal Ethical Committee of the University of Florence. Pain was measured by paw pressure and hind limb weight bearing alterations tests. MnL4 (15 mg kg −1 ) acutely administered, significantly reduced pain induced by carrageenan, complete Freund's adjuvant (CFA), and sodium monoiodoacetate (MIA). In CFA and MIA protocols, it ameliorated the alteration of postural equilibrium. When administered by osmotic pump in the MIA osteoarthritis, MnL4 reduced pain, articular derangement, plasma TNF alpha levels, and protein carbonylation. The scaffold ring was ineffective. MnL4 (10 −7  M) prevented the lipid peroxidation of isolated human chondrocytes when O 2   − was produced by RAW 264.7. MnL4 behaves as a potent pain reliever in acute inflammatory and chronic articular pain, being its efficacy related to antioxidant property. Therefore MnL4 appears as a novel protective compound potentially suitable for the treatment of joint diseases.